2008
DOI: 10.1002/humu.20732
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of genetic profiles impacting response to chemotherapy: application to gemcitabine

Abstract: For the Focus Section on PharmacogeneticsChemotherapy is a major treatment modality for individuals affected by cancer. Currently, a number of genomebased technologies are being adopted to identify genes associated with drug response; however, large-scale genetic association applications are still limited. Here we describe a novel strategy based on the genetic and drug response data of the NCI60 cell lines to discover potential candidate genetic variants associated with variable response to chemotherapy. As an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 57 publications
0
24
1
Order By: Relevance
“…Studies using these cells have successfully identified polymorphisms in candidate genes associated with drug response in vitro (Le Morvan et al, 2006;Jarjanazi et al, 2008;Puyo et al, 2008;Sasaki et al, 2008). Methylation of certain promoter CpG islands predicts toxicity to antimetabolites and alkylating agents in the NCI-60 lines (Shen et al, 2007;Sasaki et al, 2008).…”
Section: Nci-60 Cell-based Modelsmentioning
confidence: 99%
“…Studies using these cells have successfully identified polymorphisms in candidate genes associated with drug response in vitro (Le Morvan et al, 2006;Jarjanazi et al, 2008;Puyo et al, 2008;Sasaki et al, 2008). Methylation of certain promoter CpG islands predicts toxicity to antimetabolites and alkylating agents in the NCI-60 lines (Shen et al, 2007;Sasaki et al, 2008).…”
Section: Nci-60 Cell-based Modelsmentioning
confidence: 99%
“…2). The smallest antimode, observed at -6.875, was used as the cutoff value [26] between Resistant and Sensitive groups, as displayed by the vertical red line. After the above filtering steps, we produced a consolidated file containing the variant data and associated drug response values.…”
Section: Filtering and Preprocessing Of Data Setsmentioning
confidence: 99%
“…When this technique was used on three Ewing sarcoma cell lines, IGF-1, and its receptor, a series of kinases and fibroblast growth-factor receptor 4 were identified as critical for cell growth. Similar experiments can be performed in combination with cytotoxic chemotherapy to identify maximal synergies and genes related to chemoresistance 41 . Validation in primary tumor specimens, data mining, identification of biomarkers that can be used to tailor therapy to the individual patient and tumor and to monitor the response to treatment, and, ultimately, clinical trials are all part of the process.…”
Section: Novel Therapies and Regulatory Issuesmentioning
confidence: 99%
“…It was emphasized that public access to primary-expression profile data is critical as it enables external validation. Future directions may include massive parallel sequencing with ChIP (chromatin immunoprecipitation)-sequencing to survey transcriptionfactor binding across the genome, expression profiling direct from cDNA, and microRNA profiling 41 . Costs are high for equipment and data processing, analysis is complex, and standards for tissue banking need to be developed so as to not introduce artifacts into the system.…”
Section: Genomic Screening Techniquesmentioning
confidence: 99%